2014
DOI: 10.1890/13-2259.1
|View full text |Cite
|
Sign up to set email alerts
|

Having our yards and sharing them too: the collective effects of yards on native bird species in an urban landscape

Abstract: Residential yards comprise a substantial portion of urban landscapes, and the collective effects of the management of many individual yards may “scale up” to affect urban biodiversity. We conducted bird surveys and social surveys in Chicago-area (Illinois, USA) residential neighborhoods to identify the relative importance of yard design and management activities for native birds. We found that groups of neighboring yards, in the aggregate, were more important for native bird species richness than environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 68 publications
5
69
0
Order By: Relevance
“…At the most basic level, resident population is the metric used to define city size (USDC 2014). Behaviors by this key subset of urban stakeholders at the property level translate into patterns across neighborhoods and urban landscapes (Kinzig et al 2005, Cook et al 2012, Belaire et al 2014. Revealed and stated preference models (Champ et al 2003, Freeman 2003 have suggested the influence of environmental characteristics, such as water quality , open space proximity (Geoghegan 2002), trees (Donovan and Butry 2010), and green stormwater management (Ando and Freitas 2011), on property values.…”
Section: Introductionmentioning
confidence: 99%
“…At the most basic level, resident population is the metric used to define city size (USDC 2014). Behaviors by this key subset of urban stakeholders at the property level translate into patterns across neighborhoods and urban landscapes (Kinzig et al 2005, Cook et al 2012, Belaire et al 2014. Revealed and stated preference models (Champ et al 2003, Freeman 2003 have suggested the influence of environmental characteristics, such as water quality , open space proximity (Geoghegan 2002), trees (Donovan and Butry 2010), and green stormwater management (Ando and Freitas 2011), on property values.…”
Section: Introductionmentioning
confidence: 99%
“…This is consentient with MacArthur and MacArthur's (1961) classic hypothesis that it is the vertical profile of plants that drives bird species diversity given the role complex vegetation plays in many bird species' life cycles as locations for foraging and nesting. It has also been suggested, however, that increasing the ratio of conifer to deciduous species is another way to productively increase avian species diversity (Belaire et al 2014;Fontana et al 2011;Palomino and Carrascal 2006), further exemplifying the multitude of ways that a designer might productively think about incorporating structural complexity.…”
Section: Figmentioning
confidence: 99%
“…window collisions) in the United States (Loss et al 2012(Loss et al , 2013. The impacts of cat predation are significant, especially for native species (Belaire et al 2014;van Heezik et al 2010;Thomas et al 2012) and at nesting sites (Stracey 2011). Though the relative risks of predation in urban areas compared to rural environments are debated (see for example review by Shochat et al 2010) there may be other indirect impacts of predator presence in cities that negatively affect avian populations.…”
Section: Principle Three: Residential Landscapes Have Special Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transects were located !500 m apart to minimize spatial dependencies. Our study sites were primarily located in middle-to high-income neighborhoods; this sample characteristic was an artifact of selecting sites near forest preserves for a related study (Belaire et al 2014) and was not an intentional design. We collected data about both bird communities and human residents along each transect.…”
Section: Study Sitesmentioning
confidence: 99%